2017
DOI: 10.1292/jvms.17-0103
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of postoperative pain and inflammation reaction in dogs undergoing preventive laparoscopic-assisted and incisional gastropexy

Abstract: This study compared the effects of postoperative pain and inflammation reaction after preventive laparoscopic-assisted gastropexy (LAG) and incisional gastropexy (IG) in 10 clinically normal Beagles. Surgical time, incision length, visual analog scale (VAS) score, University of Melbourne Pain Scale (UMPS) score, and plasma C-reactive protein (CRP), plasma cortisol (COR), and serum interleukin-6 (IL-6) levels were evaluated. The VAS and UMPS scores and COR and IL-6 levels were recorded at 0.5, 1, 2, 4, 8, 12, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 30 publications
(33 reference statements)
1
21
0
1
Order By: Relevance
“…This finding is comparable to IL‐6 concentrations reported recently in healthy dogs using the same assay (mean, 3.0 pg/mL) . In our study population, the highest IL‐6 concentration was found, unexpectedly, in a single healthy dog with a mildly abnormal fibrosis score (F1; Table ).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…This finding is comparable to IL‐6 concentrations reported recently in healthy dogs using the same assay (mean, 3.0 pg/mL) . In our study population, the highest IL‐6 concentration was found, unexpectedly, in a single healthy dog with a mildly abnormal fibrosis score (F1; Table ).…”
Section: Resultssupporting
confidence: 90%
“…Since our research was conducted, a study of serum CRP in 46 dogs with PSS, CH, or hepatic neoplasia was published that found no differences in CRP by disease group, but did find a significant correlation between CRP and necroinflammatory activity, albeit with substantial overlap among histopathologic scores. Serum CRP is a nonspecific inflammatory marker that can increase in hospitalized dogs with a wide variety of diseases, including pancreatitis, bacterial pneumonia, and postoperative inflammation . However, CRP has been used successfully to follow response to therapy in dogs with inflammatory bowel disease or immune‐mediated polyarthritis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TNF-a regulates the release of cytokines and CRP through nuclear factor-kB activation. CRP is used to monitor the postoperative course in surgical trauma (Haraguchi et al, 2017). Its serum concentration is very low in healthy subjects but increases rapidly in cases of inflammation, infection, and traumatic injury.…”
Section: Discussionmentioning
confidence: 99%
“…Classification of studies by organ system is presented in Tables S1 and S2. Numbers of studies and participants were reported within each organ/system group including female genital tract (22 studies [n = 1407 dogs]), 1,7,11,20,30‐47 urinary tract (7 studies [n = 114]), 3,48‐53 stomach (9 studies [n = 250]), 10,18,54‐59 intestinal tract (5 studies [n = 48]), 60‐64 liver (5 studies [n = 288]), 12,17,65‐67 adrenal gland (5 studies [n = 62]), 13,28,68‐70 spleen (7 studies [n = 111]), 19,71‐76 and other (4 studies that included gastropexy and ovariectomy procedures [n = 148]) 9,77‐79 . One experimental study, in which colopexy in seven male dogs was described, was classified as intestinal tract even though these dogs were also sterilized during the surgical procedure because this study reported only complications and outcomes related to colopexy 63 .…”
Section: Resultsmentioning
confidence: 99%